2021
DOI: 10.3389/fneur.2021.647428
|View full text |Cite
|
Sign up to set email alerts
|

CSF and Serum Biomarkers of Cerebral Damage in Autoimmune Epilepsy

Abstract: Introduction: Our goal was to investigate whether biomarkers of cerebral damage are found in autoimmune-mediated epilepsy (AIE) and whether these can differentiate AIE from other seizure disorders.Methods: We retrospectively searched our cerebrospinal fluid (CSF) database for patients with definite AIE, hippocampal sclerosis due to other causes (HS), genetic generalized epilepsy (GGE), and psychogenic, non-epileptic seizures (PNES). We measured serum and CSF tau, neurofilament 1 (NFL), glial fibrillary acid pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Previous studies demonstrated that the average interictal NF-L levels in patients with drug-refractory epilepsy due to structural and other etiologies, genetic epilepsy, or temporal lobe epilepsy with hippocampal sclerosis are comparable to those in controls, although they can be slightly increased in some subpopulations of patients when using a cut-off level of 10 pg/mL [ 51 , 52 , 53 ]. Other studies, however, reported that patients with post-stroke epilepsy or epilepsy related to auto-immune encephalitis have chronically increased serum NF-L levels, even though the levels remain below 100 pg/mL [ 52 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that the average interictal NF-L levels in patients with drug-refractory epilepsy due to structural and other etiologies, genetic epilepsy, or temporal lobe epilepsy with hippocampal sclerosis are comparable to those in controls, although they can be slightly increased in some subpopulations of patients when using a cut-off level of 10 pg/mL [ 51 , 52 , 53 ]. Other studies, however, reported that patients with post-stroke epilepsy or epilepsy related to auto-immune encephalitis have chronically increased serum NF-L levels, even though the levels remain below 100 pg/mL [ 52 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“… 29 There are limited studies that discuss its usage as a serum or plasma marker in epilepsy; however, elevated serum levels have been reported in autoimmune epilepsy. 30 A study on patients with Down syndrome also reported near‐significantly higher levels in those with epilepsy. 31 Elevated serum concentrations were detected in adults with poststroke epilepsy (PSE) when compared to single seizure patients, but not in patients with non‐stroke related epilepsy.…”
Section: Blood Biomarkers Of Epilepsymentioning
confidence: 99%
“…NfL is an established clinical marker of neurodegenerative diseases, including Parkinson's disease, amyotrophic lateral sclerosis, and multiple sclerosis 29 . There are limited studies that discuss its usage as a serum or plasma marker in epilepsy; however, elevated serum levels have been reported in autoimmune epilepsy 30 . A study on patients with Down syndrome also reported near‐significantly higher levels in those with epilepsy 31 .…”
Section: Blood Biomarkers Of Epilepsymentioning
confidence: 99%
“…19 Higher levels of NfL were recently reported in patients with drug-resistant epilepsy, 20 but not in patients with autoimmune encephalitis and epilepsy. 21 NfL levels in general epilepsy populations is less well researched.…”
Section: Introductionmentioning
confidence: 99%
“…In epilepsy, NfL levels can rise after prolonged febrile seizures, 17 status epilepticus, 18 or tonic–clonic seizures 19 . Higher levels of NfL were recently reported in patients with drug‐resistant epilepsy, 20 but not in patients with autoimmune encephalitis and epilepsy 21 . NfL levels in general epilepsy populations is less well researched.…”
Section: Introductionmentioning
confidence: 99%